Can short-term heart rate variability predict coronary artery disease in patients undergoing elective coronary angiography due to typical chest pain? - Elhakeem, Ramaze Farouke (J Clin Transl Res, 2020)
BACKGROUND: Presence of typical chest pain and normal coronary angiography suggests the possibility of microvascular ischemia of the myocardium as well as other non-cardiac causes that are also likely to decrease heart rate variability (HRV). This raises a question of whether poor HRV can predict abnormal elective coronary angiography (ECA). AIM: The aim of this study was to compare HRV in patients with typical chest pain when they are classified according to ECA outcomes. METHODS: The study enrolled 150 patients planned for ECA in the cardiac center of AlShaab Teaching Hospital, Khartoum, Sudan, due to typical chest pain. Following assessment of medical history and clinical examination, the Bluetooth electrocardiography (ECG) transmitter and receiver were used for ECG recording and evaluation of time and frequency domains HRV. ECA confirmed the diagnosis of coronary artery disease (CAD) in 108 patients, who were considered as the test group. The other 42 subjects were considered as a control group after the exclusion of CAD. RESULTS: The Mean±SD of Ln(pNN10), Ln(pNN20), LnLF, and LnHF was significantly higher in subjects with normal angiography compared with CAD patients. However, these statistically significant differences disappeared when the comparison was adjusted for age, gender, BMI, and HR of the studied groups. CONCLUSION: HRV is comparable in patients with typical chest pain regardless of ECA outcomes RELEVANCE FOR PATIENTS: The HRV differences between patients with normal and abnormal ECA are likely to be biased by CAD risk factors such as old age, male gender, and tachycardia that are known to disturb HRV. The possibility of microvascular ischemia in patients with normal ECA may have attenuated HRV in this group and make it comparable to those suffering from macrovascular ischemia due to CAD.